Hydropower development in the Republic of Georgia and implications for freshwater biodiversity conservation. (November 2021) - Japoshvili, Bella; Couto, Thiago B.A.; Mumladze, Levan; Epitashvili, Giorgi; McClain, Michael E.; Jenkins, Clinton N.; Anderson, Elizabeth P.
Abstract: The Caucasus region is a meeting point for culture and nature, lying at the nexus of Europe, the Middle East, Central Asia, and Africa, and identified as one of 36 global biodiversity hotspots. The Republic of Georgia, the center of the Caucasus biodiversity hotspot, encompasses a geographically diverse landscape inhabited by a remarkable, endemic, and understudied flora and fauna under increasing threat from human activities. A wave of new and proposed dams for hydropower presents one of the most pressing challenges for freshwater biodiversity conservation in Georgia, a country where hydropower accounts for >90% of electricity. However, this situation remains largely unknown to the international scientific community and there is limited scientific information available about Georgia in the internationally indexed peer-reviewed literature. In this article, we describe the geography, politics, and freshwater biodiversity of rivers of Georgia, with a focus on fishes. We examine trends in hydropower development over the past century and identify four distinct periods: the pre-Soviet period (until 1921), the Soviet period (1921–1991), the 1990s immediately following Georgia's declaration of independence, and the 21st century. We explore the effects of existing and proposed dams on the connectivity of rivers of western Georgia and their potential consequences for conservation of diadromous, potamodromous, and resident fish. Using the Dendritic Connectivity Index (DCI) as an analytical lens, we found serial decreases in DCI values following different periods of hydropower development in the country. Finally, we offer four considerations for future research and conservation in light of ongoing hydropower development: i) expand biodiversity research and environmental monitoring, ii) assess and implement environmental flows for Georgian rivers, iii) implement strategic planning for new hydropower development, and iv) establish strict conservation areas for protection of endangered sturgeons. Highlights: The biological richness of Georgia has received limited coverage in the international conservation literature. Recent proliferation of hydropower dams presents a challenge for conservation of freshwater biodiversity. Existing dams have fragmented river connectivity in basins draining western Georgia. Both migratory and resident fishes are subjected to the impacts of hydropower dams. Georgian rivers provide critical habitat for globally threatened sturgeon species worldwiede.